Electrode slurry for heterojunction solar cell and preparation method thereof

By using a liquid phase method to prepare silver powder and adding perfluorooctane-modified graphene oxide to the electrode slurry for heterojunction solar cells, the problems of insufficient conductivity, wear resistance and corrosion resistance of the electrode slurry are solved. , achieving more stable conductivity and better durability.

CN119314721APending Publication Date: 2025-01-14NINGBO WEICHUANG FLEXIBLE ELECTRONIC TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411435652.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing electrode paste for heterojunction solar cells has shortcomings in terms of conductivity, wear resistance and corrosion resistance, and it is impossible to ensure the uniform distribution of conductive powders and the stability of the system.

Method used

Silver powder is prepared using a liquid phase method, and graphene oxide modified by perfluorooctanethiol is added to improve the conductivity, wear resistance and corrosion resistance of the modified silver powder through the reaction of sulfhydryl groups with the silver powder.

Benefits of technology

It improves the conductivity, wear resistance and corrosion resistance of the electrode slurry, ensuring the uniform distribution of conductive powder and the stability of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084878400000091
    Figure BDA0005084878400000091
Patent Text Reader

Abstract

The invention discloses electrode paste for a heterojunction solar cell and a preparation method of the electrode paste, belongs to the technical field of electronic paste, and is used for solving the technical problems that the conductivity of the electrode paste for the heterojunction solar cell prepared in the prior art cannot be remarkably improved, and the wear resistance and the corrosion resistance are poor. The electrode paste for the heterojunction solar cell disclosed by the invention comprises modified silver powder, binding phase glass powder and an organic carrier (comprising an organic solvent, a binding agent and a thixotropic agent). The modified silver powder is added with a modified additive, so that the wear resistance, corrosion resistance and conductivity of the modified silver powder are improved. Wherein the modified additive is prepared from perfluorooctanethiol which is intercalated and grafted with graphene oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to an electrode paste for a heterojunction solar cell and a preparation method thereof. Background Art

[0002] Heterojunction solar cells (HIT) are amorphous silicon thin films deposited on crystalline silicon. They combine the advantages of crystalline silicon cells and thin-film cells, and have both the good absorption performance of conventional crystalline silicon cells and the excellent passivation characteristics of thin-film amorphous silicon. Heterojunction cells have the characteristics of high potential for improving photoelectric conversion efficiency, greater cost reduction space, higher bifaciality, and lower light-induced degradation, and are one of the hot spots for investment in the next generation of solar cells. Heterojunction solar cells mainly collect and export electrons through silver grid lines printed on silicon wafers. The quality of the electrode silver paste determines its conversion efficiency, so the electrode paste plays a vital role in the production process of heterojunction solar cells.

[0003] The electrode paste used in heterojunction solar cells is mainly composed of three parts: conductive phase, organic carrier and solidified phase. The organic carrier mainly controls the fluidity and rheology in the electrode paste; the conductive phase plays a conductive role and is the main component of the electrode paste, which has the greatest impact on the performance of the silver paste. The solidified phase mainly plays a curing role in the silver paste, which can provide adhesion for the silver paste and enable the silver electrode to form a good ohmic contact with the silicon wafer. How to improve the conductivity, wear resistance and corrosion resistance of the conductive electrode paste is a technical problem that needs to be solved urgently.

[0004] Invention patent application CN114883028A discloses a method for preparing a low-temperature conductive paste for heterojunction solar cells. A micron-submicron-nanoscale and sheet-sphere composite silver-plated copper powder system is used as the conductive powder. Resin, curing agent and thixotropic agent are mixed and rolled to obtain an organic carrier. The conductive paste prepared by the present invention improves the contact conductivity of the powder by closely stacking the conductive powder; however, the physical method of stacking conductive silver powder to improve the conductivity cannot guarantee the uniform distribution of the conductive powder and the stability of the system, and thus cannot guarantee that the conductive powder has stable conductivity; in addition, the above conductive paste still cannot improve its own wear resistance and corrosion resistance.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide an electrode slurry for a heterojunction solar cell. When the above-mentioned electrode slurry is prepared by a liquid phase method, graphene oxide modified by perfluorooctanethiol is added, and the thiol group of perfluorooctanethiol reacts with the conductive silver powder to improve the conductivity, wear resistance and corrosion resistance of the electrode slurry.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] An electrode slurry for a heterojunction solar cell, the electrode slurry comprising the following materials in percentage by mass:

[0009] 70-80 parts of modified silver powder, 2-5 parts of adhesive phase glass powder and 20-25 parts of organic carrier;

[0010] The organic carrier comprises 70-80 parts of an organic solvent, 1-10 parts of a binder and 1-10 parts of a thixotropic agent.

[0011] Furthermore, the modified silver powder is prepared by the following steps:

[0012] S1, silver nitrate and deionized water are mixed and stirred until completely dissolved to obtain a silver nitrate solution; a dispersant and a modifying additive are added to the silver nitrate solution, stirred and dissolved to obtain a mixed solution;

[0013] S2. Mix hydrazine hydrate and deionized water, stir and dissolve to obtain a hydrazine hydrate solution; add the hydrazine hydrate solution drop by drop into the mixed solution using a separatory funnel, and then let the mixed solution stand for 24 hours to precipitate silver powder; the silver powder is filtered using a Buchner funnel and a vacuum pump, washed three times with deionized water, and then vacuum dried and sieved to obtain modified silver powder.

[0014] Silver nitrate is used as an oxidant and hydrazine hydrate is used as a strong reducing agent. In a liquid environment provided by deionized water, silver is reduced from its compound, and then silver powder particles are prepared through processes such as centrifugation, washing, and vacuum drying. When preparing modified silver powder, the dispersant will combine with the surface of the silver powder to form a coating layer, forcing the grains to grow uniformly along different crystal planes.

[0015] Furthermore, in S1, the usage ratio of silver nitrate, deionized water, dispersant and modifying additive is 17g:100mL:0.2-0.3g:10-20g; in S2, the usage ratio of hydrazine hydrate and deionized water is 1.5g:100mL.

[0016] Furthermore, in A1, the modified additive is prepared by the following steps:

[0017] A1. Mixing graphene powder and 10 mol / L nitric acid to obtain a mixture; heating the mixture to 40-50° C., reacting for 24 hours, and filtering to obtain a solid; washing the solid with deionized water until the pH value of the filtrate is neutral to obtain graphene oxide;

[0018] A2, graphene oxide, deionized water and perfluorooctanethiol are mixed to obtain a mixed solid-liquid; the mixed solid-liquid is ultrasonically treated, heated to reflux, and then filtered to obtain a solid; the solid is centrifuged, washed with ethanol and acetone in sequence, and then vacuum dried at 50-60° C. for 12 hours to obtain a modified additive.

[0019] Graphene itself has excellent electrical conductivity and can modify the electrical conductivity of silver powder. As a layered compound, the molecular structure of graphene oxide is rich in hydroxyl and epoxy functional groups on the base plane, while carboxyl and carboxyl functional groups exist on the edge of the sheet. Graphene oxide is mixed with perfluorooctanethiol with a thiol group. Perfluorooctanethiol can react with graphene oxide and intercalate graphene oxide, thereby preparing perfluorooctanethiol-modified graphene oxide. The thiol group on perfluorooctanethiol can react with the silver surface, so that the silver powder is grafted with organic matter containing polyfluorocarbon chains, thereby improving the wear resistance of the prepared modified silver powder.

[0020] Furthermore, in A1, the usage ratio of graphene powder and nitric acid is 5 g:50 mL; in A2, the usage ratio of graphene oxide, deionized water and perfluorooctanethiol is 5-10 g:100 mL:10-20 mL.

[0021] Furthermore, in A2, the frequency of ultrasonic treatment is 20-30 KHz, and the duration of ultrasonic treatment is 30-60 min; the temperature of heating reflux is 100-110° C., and the duration of heating reflux is 10-12 h.

[0022] Furthermore, in S2, the vacuum drying temperature is 60-70°C, the vacuum drying time is 24 hours, and the sieving mesh size is 100 mesh, 200 mesh or 300 mesh.

[0023] Furthermore, the organic solvent is any one of butyl carbitol, butyl carbitol acetate, alcohol ester dodecahydrate, tributyl citrate and their combinations; the binder is any one of ethyl cellulose, acrylic resin, nitrocellulose and their combinations; the thixotropic agent is any one of hydrogenated castor oil, polyamide wax and polyvinyl alcohol.

[0024] Furthermore, a method for preparing an electrode slurry for a heterojunction solar cell is provided, which is used for an electrode slurry for a heterojunction solar cell according to any one of claims 1 to 6, and is characterized in that it comprises the following steps:

[0025] B1. Heat the organic solvent to 60-70°C, stir at 1000-1500 rpm for 5-10 min, then add the binder, mix and stir until completely dissolved; then add the thixotropic agent, mix and stir until completely dissolved, to obtain an organic carrier;

[0026] B2. Mix the modified silver powder and the binder phase glass powder, grind them in a mortar to make them fully mixed; then add the organic carrier, stir until completely uniform to obtain a mixture; grind the mixture 3-5 times using a three-roll grinder to obtain an electrode slurry for heterojunction solar cells.

[0027] The present invention has the following beneficial effects:

[0028] 1. The electrode slurry for heterojunction solar cells prepared by the present invention is composed of three parts: functional phase silver powder, bonding phase glass powder and carrier organic carrier. The organic carrier is composed of organic solvent, binder and thixotropic agent. The electrode slurry for heterojunction solar cells obtained according to a certain ratio has good fluidity, viscosity and thixotropy.

[0029] 2. When preparing nanosilver by liquid phase method, the dispersant and the hydrophobic base of the silver powder are combined with each other to allow the silver powder to grow evenly on different crystal planes during the growth process, and the dispersant is used to control the growth structure of the silver powder; modifying additives are added to improve the conductivity, wear resistance and corrosion resistance of the nanosilver itself; the modifying additives are specifically perfluorooctanethiol grafted and intercalated graphene oxide; graphene oxide is used to improve the conductivity of the modified silver powder, and the polyfluorocarbon chain of perfluorooctanethiol is used to improve the wear resistance and corrosion resistance of the modified silver powder. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment provides a method for preparing an electrode slurry for a heterojunction solar cell, comprising the following steps:

[0033] Step 1: Preparation of modified additives

[0034] 5 g of graphene powder was added to a beaker, and then 50 mL of concentrated nitric acid was added, and the mixture was stirred for 30 min to obtain a mixture. The mixture was heated to 50 ° C, reacted for 24 h, and then filtered to obtain a solid. The solid was washed with deionized water until the pH value of the filtrate was neutral to obtain graphene oxide.

[0035] 5 g of graphene oxide, 100 mL of deionized water and 10 mL of perfluorooctanethiol were mixed to obtain a mixed solid-liquid. The mixed solid-liquid was ultrasonically treated at 20 KHz for 30 min under a nitrogen atmosphere, then refluxed at 100 ° C for 10 h, and then filtered to obtain a solid. The solid was centrifuged, washed three times with ethanol and acetone in sequence, and then vacuum dried at 50 ° C for 12 h to obtain a modified additive.

[0036] Step 2: Preparation of modified silver powder

[0037] Weigh 17 g of silver nitrate and add it into a 250 mL beaker, add 100 mL of deionized water, and rapidly stir at 100 r / min until it is completely dissolved to obtain a silver nitrate solution; add 0.2 g of a dispersant and 10 g of a modifying additive to the silver nitrate solution, stir to dissolve, and obtain a mixed solution.

[0038] Add 1.5g of hydrazine hydrate and 100mL of deionized water into a beaker, stir and dissolve to obtain a hydrazine hydrate solution. The hydrazine hydrate solution is placed on a magnetic stirrer, and the hydrazine hydrate solution is added drop by drop into the mixed solution using a separatory funnel. During the addition process, the mixed solution is stirred evenly at 100r / min; then the mixed solution is allowed to stand for 2h to precipitate silver powder. The silver powder is filtered using a Buchner funnel and a vacuum pump, then washed three times with deionized water, and then placed in a vacuum oven at 60°C and dried for 24h, and passed through a 100-mesh sieve to obtain modified silver powder.

[0039] Step 3: Preparation of electrode slurry for heterojunction solar cells

[0040] Weigh 30 parts of butyl carbitol and 40 parts of alcohol ester Twelve and place them in a 250mL beaker, transfer the beaker to a water bath, heat to 60°C, stir at 1000 rpm for 5 minutes, then add 1 part of binder ethyl cellulose, mix and stir until completely dissolved; then add 1 part of thixotropic agent hydrogenated castor oil, mix and stir until completely dissolved to obtain an organic carrier.

[0041] 70 parts of modified silver powder and 2 parts of adhesive phase glass powder were mixed and ground in a mortar to be fully mixed, and then 20 parts of an organic carrier were added and stirred until completely uniform to obtain a mixture; the mixture was ground three times using a three-roll grinder to obtain an electrode slurry for a heterojunction solar cell.

[0042] Example 2

[0043] This embodiment provides a method for preparing an electrode slurry for a heterojunction solar cell, comprising the following steps:

[0044] Step 1: Preparation of modified additives

[0045] 5 g of graphene powder was added to a beaker, and then 50 mL of concentrated nitric acid was added, and the mixture was stirred for 30 min to obtain a mixture. The mixture was heated to 45°C, reacted for 24 h, and then filtered to obtain a solid; the solid was washed with deionized water until the pH value of the filtrate was neutral to obtain graphene oxide.

[0046] 8 g of graphene oxide, 100 mL of deionized water and 15 mL of perfluorooctanethiol were mixed to obtain a mixed solid-liquid. The mixed solid-liquid was ultrasonically treated at 25 KHz for 40 min under a nitrogen atmosphere, then refluxed at 105°C for 11 h, and then filtered to obtain a solid; the solid was centrifuged, washed three times with ethanol and acetone in sequence, and then vacuum dried at 55°C for 12 h to obtain a modified additive.

[0047] Step 2: Preparation of modified silver powder

[0048] Weigh 17 g of silver nitrate and add it into a 250 mL beaker, add 100 mL of deionized water, and stir rapidly at 100 r / min until it is completely dissolved to obtain a silver nitrate solution; add 0.2-0.3 g of a dispersant and 15 g of a modifying additive to the silver nitrate solution, stir to dissolve, and obtain a mixed solution.

[0049] Add 1.5g of hydrazine hydrate and 100mL of deionized water into a beaker, stir and dissolve to obtain a hydrazine hydrate solution. The hydrazine hydrate solution is placed on a magnetic stirrer, and the hydrazine hydrate solution is added drop by drop into the mixed solution using a separatory funnel. During the addition, the mixed solution is stirred evenly at 100r / min. The mixed solution is then allowed to stand for 3h to precipitate silver powder. The silver powder is filtered using a Buchner funnel and a vacuum pump, then washed three times with deionized water, and then placed in a vacuum oven at 65°C and dried for 24h, and sieved through a 200-mesh sieve to obtain modified silver powder.

[0050] Step 3: Preparation of electrode slurry for heterojunction solar cells

[0051] Weigh 36 parts of butyl carbitol acetate and 40 parts of alcohol ester twelve and place them in a 250mL beaker, transfer the beaker to a water bath, heat to 65°C, stir at 1200 rpm for 8 minutes, then add 6 parts of binder acrylic resin, mix and stir until completely dissolved; then add 1 part of thixotropic agent polyamide wax 5 powder, mix and stir until completely dissolved to obtain an organic carrier.

[0052] 75 parts of modified silver powder and 4 parts of adhesive phase glass powder were mixed and ground in a mortar to be fully mixed, and then 22 parts of an organic carrier were added and stirred until completely uniform to obtain a mixture; the mixture was ground 4 times using a three-roll grinder to obtain an electrode slurry for a heterojunction solar cell.

[0053] Example 3

[0054] This embodiment provides a method for preparing an electrode slurry for a heterojunction solar cell, comprising the following steps:

[0055] Step 1: Preparation of modified additives

[0056] 5 g of graphene powder was added to a beaker, and then 50 mL of concentrated nitric acid was added, and the mixture was stirred for 30 min to obtain a mixture. The mixture was heated to 50 ° C, reacted for 24 h, and then filtered to obtain a solid. The solid was washed with deionized water until the pH value of the filtrate was neutral to obtain graphene oxide.

[0057] 10 g of graphene oxide, 100 mL of deionized water and 20 mL of perfluorooctanethiol were mixed to obtain a mixed solid-liquid. The mixed solid-liquid was ultrasonically treated at 30 KHz for 60 min under a nitrogen atmosphere, then refluxed at 110 ° C for 12 h, and then filtered to obtain a solid. The solid was centrifuged, washed three times with ethanol and acetone in sequence, and then vacuum dried at 60 ° C for 12 h to obtain a modified additive.

[0058] Step 2: Preparation of modified silver powder

[0059] Weigh 17 g of silver nitrate into a 250 mL beaker, add 100 mL of deionized water, and stir rapidly at 100 r / min until completely dissolved to obtain a silver nitrate solution. Add 0.3 g of a dispersant and 20 g of a modifying additive to the silver nitrate solution, stir and dissolve to obtain a mixed solution.

[0060] Add 1.5g of hydrazine hydrate and 100mL of deionized water into a beaker, stir and dissolve to obtain a hydrazine hydrate solution; place the hydrazine hydrate solution on a magnetic stirrer, and use a separatory funnel to add the hydrazine hydrate solution drop by drop into the mixed solution. During the addition, the mixed solution is stirred evenly at 100r / min. Then the mixed solution is allowed to stand for 4h to precipitate silver powder. The silver powder is filtered using a Buchner funnel and a vacuum pump, then washed three times with deionized water, and then placed in a vacuum oven at 70°C to dry for 24h, and sieved through a 300-mesh sieve to obtain modified silver powder.

[0061] Step 3: Preparation of electrode slurry for heterojunction solar cells

[0062] Weigh 40 parts of butyl carbitol and 40 parts of tributyl citrate and place them in a 250 mL beaker, transfer the beaker to a water bath, heat to 70°C, stir at 1500 rpm for 10 min, then add 1 part of binder nitrocellulose, mix and stir until completely dissolved; then add 1 part of thixotropic agent polyvinyl alcohol, mix and stir until completely dissolved to obtain an organic carrier.

[0063] 80 parts of modified silver powder and 5 parts of binder glass powder were mixed and ground in a mortar to be fully mixed, and then 25 parts of organic vehicle were added and stirred until completely uniform to obtain a mixture. The mixture was ground 5 times using a three-roll mill to obtain an electrode slurry for a heterojunction solar cell.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 3 is that in step 1, the graphene oxide is not modified with perfluorooctanethiol.

[0066] Comparative Example 2

[0067] The difference between this comparative example and Example 3 is that in step 2, no modifying additive is added to the silver nitrate solution.

[0068] Performance Test:

[0069] 1. The electrode slurries prepared in Examples 1-3 and Comparative Examples 1-2 were sprayed on the surface of the PET film using an M-3 handheld four-probe tester, and then the surface square resistance test was performed. The volume resistivity of the coating was calculated.

[0070] ρ=R S ·d

[0071] Where, ρ is the volume resistivity of the coating; R S is the surface resistance of the coating; d is the thickness of the coating.

[0072] 2. According to GJB150.11-86 "Environmental Test Methods for Military Equipment - Salt Spray Test", the electrode slurries prepared in Examples 1-3 and Comparative Examples 1-2 were sprayed on tinplate to obtain a coating; the coating was tested for neutral salt spray resistance and the corrosion resistance time of the coating was recorded. The test temperature was controlled to be 35°C and the concentration of the NaCl solution was 5%wt. The corrosion resistance time of the coating prepared in Example 1-3 and Comparative Example 1-2 was recorded.

[0073] The specific test results are shown in the table below:

[0074] Table 1

[0075]

[0076] Data Analysis:

[0077] Analyzing the data in Table 1, the volume resistivity values ​​of the electrode slurries for heterojunction solar cells prepared in Examples 1-3 of the present invention are small, and all have excellent conductivity. However, as the proportion of the modifying additive in the modified silver powder increases, the volume resistivity value of the electrode slurry for heterojunction solar cells increases, which is not conducive to improving the conductivity of the electrode slurry; however, the increase in the content of the modifying additive in the electrode slurry helps to improve the corrosion resistance of the prepared electrode slurry, which is manifested as the extension of the corrosion resistance time of the coating. However, in Comparative Example 1, the graphene oxide was not modified with perfluorooctanethiol, and no modifying additive was added when preparing the silver powder in Comparative Example 2, which damaged the corrosion resistance of the coating.

[0078] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0079] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0080] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An electrode slurry for heterojunction solar cells, characterized in that: The electrode slurry comprises the following components in parts by weight: 70-80 parts of modified silver powder, 2-5 parts of adhesive phase glass powder and 20-25 parts of organic carrier; The organic carrier comprises, by weight: 70-80 parts of an organic solvent, 1-10 parts of a binder and 1-10 parts of a thixotropic agent.

2. The electrode slurry for heterojunction solar cells according to claim 1, characterized in that: The modified silver powder is prepared by the following steps: S1, silver nitrate and deionized water are mixed and stirred until completely dissolved to obtain a silver nitrate solution; a dispersant and a modifying additive are added to the silver nitrate solution, stirred and dissolved to obtain a mixed solution; S2, mixing hydrazine hydrate and deionized water, stirring and dissolving to obtain a hydrazine hydrate solution; The hydrazine hydrate solution was added dropwise into the mixed solution using a separatory funnel, and the mixed solution was then allowed to stand for 24 hours to precipitate silver powder; the silver powder was filtered using a Buchner funnel and a vacuum pump, washed three times with deionized water, and then vacuum dried and sieved to obtain modified silver powder.

3. The electrode slurry for heterojunction solar cells according to claim 2, characterized in that: In S1, the usage ratio of silver nitrate, deionized water, dispersant and modifying additive is 17g:100mL:0.2-0.3g:10-20g; in S2, the usage ratio of hydrazine hydrate and deionized water is 1.5g:100mL.

4. The electrode slurry for heterojunction solar cells according to claim 2, characterized in that: In A1, the modified additive is prepared by the following steps: A1. Mixing graphene powder and 10 mol / L nitric acid to obtain a mixture; heating the mixture to 40-50° C., reacting for 24 hours, and filtering to obtain a solid; washing the solid with deionized water until the pH value of the filtrate is neutral to obtain graphene oxide; A2, graphene oxide, deionized water and perfluorooctanethiol are mixed to obtain a mixed solid-liquid; the mixed solid-liquid is ultrasonically treated, heated to reflux, and then filtered to obtain a solid; the solid is centrifuged, washed with ethanol and acetone in sequence, and then vacuum dried at 50-60° C. for 12 hours to obtain a modified additive.

5. The electrode slurry for heterojunction solar cells according to claim 4, characterized in that: In A1, the usage ratio of graphene powder and nitric acid is 5g:50mL; in A2, the usage ratio of graphene oxide, deionized water and perfluorooctanethiol is 5-10g:100mL:10-20mL.

6. The electrode slurry for heterojunction solar cells according to claim 4, characterized in that: In A2, the frequency of ultrasonic treatment is 20-30 KHz, and the duration of ultrasonic treatment is 30-60 min; the temperature of heating reflux is 100-110° C., and the duration of heating reflux is 10-12 h.

7. The electrode slurry for heterojunction solar cells according to claim 2, characterized in that: In S2, the vacuum drying temperature is 60-70° C., the vacuum drying time is 24 h, and the sieving mesh size is 100 mesh, 200 mesh or 300 mesh.

8. The electrode slurry for heterojunction solar cells according to claim 1, characterized in that: The organic solvent is any one of butyl carbitol, butyl carbitol acetate, alcohol ester dodecahydrate, tributyl citrate and their combinations; the binder is any one of ethyl cellulose, acrylic resin, nitrocellulose and their combinations; the thixotropic agent is any one of hydrogenated castor oil, polyamide wax and polyvinyl alcohol.

9. The electrode slurry for heterojunction solar cells according to claim 1, characterized in that: A method for preparing an electrode slurry for a heterojunction solar cell, used for an electrode slurry for a heterojunction solar cell as claimed in any one of claims 1 to 6, characterized in that it comprises the following steps: B1. Heat the organic solvent to 60-70°C, stir at 1000-1500 rpm for 5-10 min, then add the binder, mix and stir until completely dissolved; then add the thixotropic agent, mix and stir until completely dissolved, to obtain an organic carrier; B2. Mix the modified silver powder and the binder phase glass powder, grind them in a mortar to make them fully mixed; then add the organic carrier, stir until completely uniform, and obtain a mixture; grind the mixture 3-5 times using a three-roll grinder to obtain an electrode slurry for heterojunction solar cells.

Citation Information

Patent Citations

  • Low-temperature conductive paste for heterojunction solar cell and preparation method of low-temperature conductive paste

    CN114883028A

  • Post-treatment protective agent for rare and precious metals

    CN101974759A

  • Conductive composition, transparent conductive film, display element and integrated solar battery

    CN102804064A

  • Front electrode silver paste for solar battery, silver powder and preparation method thereof

    CN109215829A

  • Graphene and nano-silver composite material and preparation method thereof

    CN113563759A